Risk factors for urinary tract infection in infants with unexplained hyperbilirubinemia: a single center case-control study - Chen, Ing; Hsu, Li-Sang; Yao, Cai-Sin; Chang, Jenn-Tzong; Wang, Hsiao-Ping; Fang, Nai-Wen (Frontiers in Pediatrics, 2024)
Background: Urinary tract infection (UTI) is a potential cause of neonatal jaundice. Nevertheless, there remains a lack of consensus regarding appropriate screening practices for UTI in infants with hyperbilirubinemia. This study aimed to analyze a group of jaundiced infants to assess the prevalence of UTI, explore potential risk factors, and examine the impact of UTI on the course and severity of neonatal jaundice.Methods: This retrospective case-control study was conducted on 150 jaundiced infants (aged < 8 weeks) without a known etiology in the hyperbilirubinemia work-up. All subjects underwent phototherapy treatment and UTI screening by catheterization. They were then classified into UTI and non-UTI groups based on urine culture results, with a positive urine culture indicating the growth of ≥ 10,000 colony-forming units. The clinical characteristics and jaundice-related parameters of both groups were analyzed.Results: Among the 150 jaundiced patients, the prevalence of UTI was 29%. There was a significantly higher male predominance in the UTI group, and patients with UTI also had a significantly longer duration of hospitalization compared to those without UTI. Significant risk factors associated with UTI in jaundiced infants included male gender and a peak total bilirubin level higher than 18 mg/dL during hospitalization. The most common pathogens identified in urine culture were Escherichia coli (41.9%) and Enterococcus faecalis (30.2%).In cases of neonatal jaundice where the underlying cause is not evident, screening for UTI should be performed, particularly when associated risk factors or inadequate response to phototherapy is present.